Effects of salinity on the survival and histology of oysters Crassostrea gasar (Adanson, 1757) - Aline Horodesky; Gisela Geraldine Castilho-Westphal; Nathieli Cozer; Vitor Gomes Rossi; Antonio Ostrensky (Bioscience Journal, 2018)
Water salinity is among the most important factors influencing the distribution, abundance, growth, and survival of Crassostrea gasar, an important aquaculture resource grown in estuarine environments in diverse regions of the world. The goal of the present work was to evaluate the effects of different salinities on survival and the tissues of C. gasar under laboratory conditions. Two experiments were performed using adult oysters from five marine farms located in the bay of Guaratuba, Brazil. In Experiment 1, the daily survival rates were evaluated after the oysters were submitted to gradual acclimatization at salinities ranging from 0 to 65 gL-1 and maintained in the laboratory without feeding for up to 365 days. In Experiment 2, the oysters were exposed to salinity from 0 to 50 gL-1 for up to 30 days without feeding and possible histological alterations caused by salinity were assessed. Three tolerance ranges of C. gasar to salinity were identified: "Optimal" (between 4 and 40 gL-1), "Tolerable" (between 2.1 and 3.9 and between 41 and 50 gL-1) and "Intolerable" (less than 2 and greater than 50 gL-1). No evidence of histological alterations was observed in oysters exposed to the different salinities.